URGENSITAS PERAN OTORITAS JASA KEUANGAN (OJK) IMPLEMENTASINYA DALAM ‘PASAR’ INDUSTRI KEUANGAN DAN PERTI EKONOMI - Fatihudin, Didin (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2014)
Financial services authority (FSA) representing the government in the financial services industry market stabilization. FSA has the freedom to make decisions and non-government managers. FSA oversees banking products, investment and finance. FSA is expected to direct economic activity (market) on the path to equality and welfare of Indonesian society as a whole. If the FSA's role is broader than the previous institutions function, then it should be the orientation of the curriculum of courses in economics faculty also need to change and be expanded with the development of other empirical level.